2-D FM-IBEM Simulation of broadband ground motions on near-fault mountain-valley coupling site. (December 2022) - Liu, Zhongxian; Zhou, Tao; Meng, Sibo; Jin, Liguo
Abstract: In this study, a fast multipole indirect boundary element method (FM-IBEM) was used to efficiently simulate broadband ground motions of complex sites near faults. The spatial distribution of ground motion at the mountain-valley coupling site located on the hanging wall of the strike-slip fault was quantitatively investigated. The kinematic source model was employed to simulate the fault rupture, and the scattering by the mountain-valley site was solved by the FM expansion and GMRES iterative technique. The influence of mountains on the seismic response of a valley was investigated. The effects of the fault distance and depth on the seismic response of the mountain-valley site were also studied. Moreover, the method was applied to simulate the seismic response of the location of the Liuhuanggou Bridge during the Menyuan earthquake. The results show that mountains have a "shielding effect" on near-fault waves, and valleys have a significant amplification effect on near-fault waves, especially in the 0–1 Hz frequency band. The spatial distribution of ground motion is complex owing to the near-fault and local site effects. A reasonable explanation for the seismic damage to the bridge at Liuhuanggou during the Menyuan earthquake is the significant phase difference in the spatial distribution caused by the surface waves